English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

Given ax² + bx + c = 0, the quadratic formula tells us that:

x = [ -b ± √(b²-4ac) ] ÷ 2a

In your problem, a=3, b=12, c=1 -- simply plug these values into the quadratic formula to solve for x.

2006-11-05 13:44:29 · answer #1 · answered by dualspace 3 · 0 0

x=12

2006-11-05 21:54:32 · answer #2 · answered by fritters1018 1 · 0 0

3x^2 + 12x + 1 = 0

x = (-b ± sqrt(b^2 - 4ac))/(2a)

x = (-12 ± sqrt(12^2 - 4(3)(1)))/(2(3))
x = (-12 ± sqrt(144 - 12))/6
x = (-12 ± sqrt(132))/6
x = (-12 ± sqrt(4 * 33))/6
x = (-12 ± 2sqrt(33))/6
x = (1/3)(-6 ± sqrt(33))

ANS :

x = (1/3)(-6 + sqrt(33)) or (1/3)(-6 - sqrt(33))

2006-11-05 23:29:47 · answer #3 · answered by Sherman81 6 · 0 0

I was wrong. First answer is correct.

2006-11-05 21:48:41 · answer #4 · answered by Honey 3 · 0 0

fedest.com, questions and answers